(3GdbWGY GdeUQaj hGdGbJUGO GdhWfj GdbWGY GdeUQaj hZSjd GdGehGd (B/s - (3GdSjSj, UdGM GdOjf MSfs ((3GdbGgQI(B: s (3GdgjFI GdeUQjI GdYGeI ddcJGH(B, s, 2003)
(3jJfGhd GdcJGH ehVhYjf aj ZGjI GdCgejI, ef GdfGMjI GdGbJUGOjI, hjJYdb GdChd HGdbWGY GdeUQaj hGdGbJUGO GdhWfj, hjTed GdHfhc hGdJfejI GdGbJUGOjI, hGdGFJeGf GdeUQaj ddeTQhYGJ, hWQb Jehjd GdHfhc ddeTQhYGJ, hGdJhLg GdYGdej fMh GdeUGQa GdTGedI aj Xd efXeI GdJLGQI GdYGdejI(B. (3hjJYdb GdKGfj HehVhY GdbWGY GdeUQaj hXGgQI ZSjd GdCehGd, hGdGJLGgGJ GdOhdjI fMh ecGaMI ZSjd GdCehGd, hGdBKGQ GdGbJUGOjI GdeJQJHI Ydi gPg GdXGgQI (B.s
(3HjHdjhZQGajG (B: (3U(B. 208s
Keywords: (3GdGbJUGOs; (3GdHfhcs; (3JHjjV GdGehGds; (3LQGFe GdCehGds